Community Empowerment for Stunting Prevention: Moringa Brownies and Tempeh for Pregnant Women in South Lampung - Sefanadia Putri; Reni Indriyani; Arie Nugroho (Sarana Ilmu Indonesia (salnesia), 2026)
The high prevalence of anemia among pregnant women and the risk of stunting in Tanjungsari Village, South Lampung, motivated this Community Service (PKM) activity. This program aimed to empower the community through nutritional education and training on processing local food resources (Moringa leaves and tempeh). The implementation method employed a participatory approach, comprising education on the First 1000 Days of Life and practical demonstrations of making “Moringa and Tempeh Brownies.” Evaluation results showed significant improvements in both cognitive and psychomotor aspects. The participants' average knowledge score increased by 15.7% (from 7.78 to 9.00), with 80% of participants achieving a